Global Catastrophes : A Very Short Introduction - McGuire, Bill, 1954- (Oxford, New York Oxford Univ. Press, 2014)
In this Very Short Introduction Bill McGuire explores the potential catastrophes facing our planet. Assessing both the probability of these events happening in the future, and our chances of survival, this new edition brings our understanding of global disasters and risk research up to date, by using recent case studies from around the world.
Include Index and Illustration
Keywords: Natural disasters